PENYULUHAN TENTANG MANFAAT DAUN KELOR TERHADAP LUKA BAKAR DI PUSKESMAS TANJUNG MORAWA - Wahyudi Wahyudi; Palas Tarigan (INSTITUT KESEHATAN DELI HUSADA, 2021)
Direction on the benefits of kelor leaf for the burn treatment at the cape morawa center was shown to apply the information and development students acquired in broader local conversations. To the burns at cape morawa center. The kelor leaf (moringa oleifera lam) has many health benefits, one of which is the burning skin. Burns are tissue damage caused by contact with hot sources, such as fire, hot water, chemicals, electricity, and radiation. Burns are found in skin, mucus membranes, respiratory tract, and digestive tract. Symptoms of pain, swelling, red, abrasions. The most improved thing to do with burns is to provide local therapy with the intention of recovering as quickly as possible. The reason for this PKM is to get data on the kelor leaf application (moringa oleifera lam). Flavonoid and leaf leaf tannin play a role in treating burns.